STUDENT BUSINESS DEVELOPMENT AND SUSTAINABILITY - Indra Hastuti; Indah Wahyu Utami; Sopingi Sopingi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The entrepreneurship development program aims to foster and assist students who already have a business or are just starting a business so that their business develops and is sustainable. Business development and business sustainability of students are highly expected because many businesses have been carried out by students with very interesting ideas and creativity, but the business carried out did not last long for various reasons of busy completing college, thesis and others. Their problems are limited manpower, lack of cooperation with partners and unsustainable marketing. The method of implementing entrepreneurship development program activities for students is to provide socialization of activities, provide training in Human Resource Management, Financial Management, online marketing, use of the UDB Market place, workshops on making web designs followed by mentoring, business visits, and business bazaars to introduce products. The result of this Entrepreneurship Development Program activity is to make 20 student tenants have independent and growing and sustainable businesses. Keywords: Development, sustainability, entrepreneurship, independent business